Agents’ Perception towards Life Insurance Corporation With Reference To Perambalur District in Tamilnadu - *, RAngayarkanni; Swaminathan, DrR (IJRDO - Journal of Business Management, 2017)
Life Insurance Corporation of India, the capital intensive business, provides the most important financial instrument to customers aimed at protection as well as long term savings. The Corporation reaches out to the people through the main traditional route of the agency model for the selling processes of the numerous complex need-based products. The agents help in marketing its policies by spreading the message of life insurance among the masses. They serve as the kingpin for insurance companies seeking to provide traditional and innovative products, and focal point for customers seeking to procure insurance coverage and long term savings. The present paper investigates the factors influencing agents’ perception towards Life Insurance Corporation of India. The study is based on a sample of 100 respondents taken from three cities of Perambalur District . Factor Analytic Approach has been performed for data analysis. The results of the factor analysis reveal that Staff co-ordination is the most important factor to influence agents’ perception followed by other six factors namely: (i) Customer target; (ii) Competitive advantage predicates; (iii) Material hallmarks; (iv)Promising products and process; (v) Service enhancement; and (vi) Exclusive attention. Moreover, analysis of one way classification has also been performed to test the significant differences among the various groups of respondents across the 23-item perception scale. The results demonstrate that no significant differences exist among various groups of respondents with respect to their perception towards Life Insurance Corporation of India